Best Answer

f(x)=6x2+7x+2

f(x)=(6x+1)(x+2)

x= -1/6 and x= -2

The above answer is not correct. (6x+1)(x+2) yields 6x2+13x+2, not the original equation.

The answer can be arrived at using the quadratic equation, where ax2+bx+c=0 and

x=[-b (+-) square root(b2-4ac)] / 2a

x=[-7(+-) square root (72-4(6)(2))] / 2(6)

x=[-7(+-)square root(49-48)]/12

x=[-7(+-)1]/12

x=-1/2 and -2/3

🙏

🤨

😮

Study guides

☆☆

Q: What is the answer to 6x squared plus 7x plus 2?

Write your answer...

Submit

Still have questions?

Related questions

5(7x^2y + 6x^2 + 8)

7x + 2 = 6x + 2 if and only x = 0.

(2x + 1)(3x +2)

7x + 7 + 6x - 9 = 13x - 2

7x + 2

6x - 14 + 15x + 2 =21x - 12or3 (7x - 4)

12

If you mean: 6x^2 +7x-3 then it is (2x+3)(3x-1) when factored

7x + 2 = 158 - 6x7x + 2 + 6x = 158 - 6x + 6x13x + 2 - 2= 158 - 213x / 13 = 156/13x = 12

5x2+ 7x + 2 = (x + 1)(5x + 2).

X=2

x=-7/13

(6x + 1)(x + 2)

11

7x-4=x+2 7x=x+2+4 7x=x+6 7x-x=6 6x=6 X=1

x2 + 6x + 8 =(x + 2)(x +4)

what is 7x to the third power + 6x to the second - 2

-2

No

6x^2 -13x+6 = (3x-2)(2x-3) when factorized

(x2 + 7x - 18) = (x + 9)(x - 2)

You would factor 2x2 + 7x + 6 into (2x + 3) (x+2)

49x2 - 84x + 36 = (7x - 6)(7x - 6) or (7x - 6)2

(x + 5)(x + 2)

2(x^2 + 2)(x + 3)